On entropies and complexity for amenable actions groups - Meson, Alejandro Mario (2018)
We consider a definition of entropy for discrete amenable action groups and extend the equality between enreopy and dimension for amenable groups. This last result was proved by Simpson for the special case of Z^d-actions